2017
DOI: 10.1016/j.jot.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of mesenchymal stem cells in osteoarthritis treatment

Abstract: SummaryAs the most common form of joint disorder, osteoarthritis (OA) imposes a tremendous burden on health care systems worldwide. Without effective cure, OA represents a unique opportunity for innovation in therapeutic development. In contrast to traditional treatments based on drugs, proteins, or antibodies, stem cells are poised to revolutionize medicine as they possess the capacity to replace and repair tissues and organs such as osteoarthritic joints. Among different types of stem cells, mesenchymal stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 92 publications
(134 reference statements)
0
73
0
3
Order By: Relevance
“…Bone marrow mesenchymal stem cells (BMSCs) are pluripotent cells with the capability of self‐proliferation and multi‐differentiation . Much attention has been paid to their therapeutic efficacy in regenerative medicine, as BMSCs have proved to secrete neurotrophic cytokines and anti‐inflammatory molecules . Recent studies have demonstrated that a paracrine mechanism plays a pivotal role in the therapeutic effects for stem cell transplantation, which puts exosomes in the research hotspot .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow mesenchymal stem cells (BMSCs) are pluripotent cells with the capability of self‐proliferation and multi‐differentiation . Much attention has been paid to their therapeutic efficacy in regenerative medicine, as BMSCs have proved to secrete neurotrophic cytokines and anti‐inflammatory molecules . Recent studies have demonstrated that a paracrine mechanism plays a pivotal role in the therapeutic effects for stem cell transplantation, which puts exosomes in the research hotspot .…”
mentioning
confidence: 99%
“…13 Much attention has been paid to their therapeutic efficacy in regenerative medicine, as BMSCs have proved to secrete neurotrophic cytokines and anti-inflammatory molecules. 14,15 Recent studies have demonstrated that a paracrine mechanism plays a pivotal role in the therapeutic effects for stem cell transplantation, which puts exosomes in the research hotspot. 16 Exosomes are 40-150 nm in diameter extracellular vesicles originating from multivesicular bodies, such as stem cells and cerebrospinal fluid.…”
mentioning
confidence: 99%
“…As a result, a myriad of MSC delivery strategies have been developed over the last decade to enhance articular cartilage repair and, ultimately, to delay OA. Our understanding of MSCs for the treatment of OA has improved on the basis of preclinical animal models that have demonstrated reparative effects of MSCs for meniscus, cartilage, and bone repair . The therapeutic application of MSCs is in the early stage of clinical translation; however, for the field to develop further, standardized protocols for MSC banking and expansion need to be carefully considered before clinical translation .…”
Section: Stem Cell Therapy Bone Marrow Concentrate Lipoaspirate Anmentioning
confidence: 99%
“…Long‐term cultivation has been shown to reduce the differentiation potential and cause permanent morphological changes . Despite these limitations, there are a growing number of clinical trials testing MSCs for OA using different delivery approaches . The results generated from these studies may fulfill regulatory needs and demonstrate their safety and effectiveness …”
Section: Stem Cell Therapy Bone Marrow Concentrate Lipoaspirate Anmentioning
confidence: 99%
See 1 more Smart Citation